Strategi Misi Digital Church - Andalangi, Julinda; Mundung, Arjuna; Dalonto, Chriswandy; Lintong, Aprilia (LIMMUD: Jurnal Ilmu Keagamaan dan Sosial Humaniora, 2025)
Digital transformation has significantly changed the way the church carries out its role and mission in modern society. This article discusses the importance of adaptive ministry strategies in response to technological developments, particularly in the context of the digital church. This study employs a descriptive qualitative approach to explore the lifestyle of digital congregations, the challenges of virtual ministry, and the missiological opportunities within the metaverse era. The findings reveal that digital ministry faces various challenges, such as disparities in digital literacy, data security risks, and shallow congregational relationships. Nevertheless, digitalization also presents great opportunities for the church to expand its reach through social media, hybrid worship, and virtual platforms. Therefore, the church must implement contextual, creative, and participatory strategies by involving younger generations and competent digital teams. With proper adaptation and continuous innovation, the church can remain relevant in proclaiming the Gospel and expanding its ministry impact in a dynamic digital world.